USULAN PROGRAM PENGEMBANGAN PEMASARAN UNTUK MENINGKATKAN EFEKTIVITAS PRODUKSI PADA KOPERASI KAMPUNG JAHIT NUSANTARA - P, Agatha Zelda Geraldine; Salsabila, Amalia Putri; Putri S, Anastasia Claudi Reta; Yurizki, Mufida Aqila; Athallah, Muhammad Rizky; Rasyidah, Nazwa Nur; Agustina, Tri Siwi; Hardi, John; Fitdiarini, Noorlaily; Sudarwito, Gurun (Jurnal Penyuluhan dan Pemberdayaan Masyarakat, 2024)
This research explores the role of MSMEs in improving Indonesia's socioeconomic conditions, with a focus on Kampung Jahit Nusantara Cooperative in Surabaya. MSMEs play an important role in absorbing labor, increasing GDP, and helping poor families escape poverty. The Kampung Jahit Nusantara Cooperative, based on labor-intensive housing, provides economic opportunities for local residents and improves the lives of poor families. Despite their positive contributions, these MSMEs face several challenges, such as weak reserve funds, unstructured financial reports, lack of digital marketing, low product quality, and lack of knowledge regarding employee manners. This research was conducted through field observations, interviews, and SWOT analysis. The results show that MSMEs have the potential to improve Indonesia's socio-economic conditions, but need to overcome some of the challenges faced.